9500 Nights of Mid-Infrared Observations of SN 1987A: the birth of the remnant. Issue Volume 9:Issue S296(2013) (29th January 2014) - Bouchet, Patrice; Danziger, John
Abstract: The one-in-a-life-time event Supernova SN 1987A, the brightest supernova seen since Kepler's in 1604, has given us a unique opportunity to study the mechanics of a supernova explosion and now to witness the birth of a supernova remnant. A violent encounter is underway between the fastest-moving debris and the circumstellar ring: shocks excite "hotspots". ATCA/ANTF, Gemini, VLT, HST, Spitzer, Chandra, and recently ALMA observations have been so far organized to help understanding the several emission mechanisms at work. In the mid-infrared SN 1987A has transformed from a SN with the bulk of its radiation from the ejecta to a SNR whose emission is dominated by the interaction of the blast wave with the surrounding interstellar medium, a process in which kinetic energy is converted into radiative energy. Currently this remnant emission is dominated by material in or near the inner equatorial ring (ER). We give here a brief history of our mid-infrared observations, and present our last data obtained with the SPITZER infrared satellite and the ESO VLT and Gemini telescopes: we show how together with Chandra observations, they contribute to the understanding of this fascinating object. We argue also that our imaging observations suggest that warm dust is still present in the ejecta, and we dispute the presence of huge amount of very cold dust in it, as it has been claimed on the basis of data obtained with the HERSCHELl satellite.